2019
DOI: 10.3390/ma13010010
|View full text |Cite
|
Sign up to set email alerts
|

CFRP Reinforced Foam Concrete Subjected to Dynamic Compression at Medium Strain Rate

Abstract: Carbon fiber-reinforced polymer (CFRP)-confined foam concrete can be applied in structure protection, e.g., as an impact barrier of bridge piers, in which it is used as the core of the composite impact barrier. Applying CFRP to the foam concrete exterior enhances both the CFRP and the foam concrete, leading to improved compressive performance due to their interaction. In the present study, the carbon-fiber reinforced polymer (CFRP) confining effect on the response and energy absorption of foam concrete subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The sample was cooled with air at a rate of about 7 K/min. The crystallization temperature was determined at the intersection of the slopes fitted on the specific volume in the melt state and during crystallization, as reported in the literature [31,38]. The samples showed no signs of thermal degradation (color change) after removal.…”
Section: Pressure-volume-temperature Measurement (Pvt)mentioning
confidence: 99%
“…The sample was cooled with air at a rate of about 7 K/min. The crystallization temperature was determined at the intersection of the slopes fitted on the specific volume in the melt state and during crystallization, as reported in the literature [31,38]. The samples showed no signs of thermal degradation (color change) after removal.…”
Section: Pressure-volume-temperature Measurement (Pvt)mentioning
confidence: 99%
“…The results and comparisons made during realization of a comprehensive experimental research program on samples of plain concrete and concrete strengthened by FRP can be found in [6]. Strengthening with carbon fibre-reinforced polymers was investigated by Wang Lu Liu et al [7], who experimentally investigated and compared the response, failure mode, and energy absorption of foam concrete with and without CFRP confinement, when subjected to quasi-static and dynamic loading. Several important outcomes were achieved in this study:…”
Section: Introductionmentioning
confidence: 99%
“…Under the service life of a concrete structure, it is not only subjected to static load but also may be subjected to dynamic load. Therefore, it is a need to study the dynamic behavior of concrete [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, SCC not only bears the static load, but also bears dynamic loads, such as earthquake, wind, impact and explosion, etc, under which circumstances the SCC exhibits obvious strain rate effect [ 27 , 28 ], i.e., the mechanical properties of SCC are influcenced by the strain rate. Therefore, the research of concrete dynamic performance has extremely value of civil engineering [ 4 , 5 , 29 ]. However, almost all the previous studies on the dynamic properties of concrete are focused on ordinary concrete.…”
Section: Introductionmentioning
confidence: 99%